Territorial disparities in hungarian tourism 2003 - 2013 - Béres-Virág, Ágnes; Vinogradov, Szergej (Studia Mundi – Economica, 2018)
In recent years the demand to Hungary has been increasing, the domestic and international tourism is more significant. During our survey we examined how smooth the touristic performance in our country, which are the most visited settlement and what rural areas could/can benefit from the operation of tourism. We also considered it important to examine whether the economic role of tourism can be detected along with statistical data.